GENDER’S VISIBILITY IN TEXTBOOKS - Nasrullah Nasrullah (Politeknik Negeri Bengkalis, 2016)
Abstract: The problems of gender are occurred in almost all aspects of social real-life. In fact, discourse is also reflected in textbooks used by schools. In a specific talk, there are various perspectives presented to address gender particularly gender bias in textbook suchas through typology (initiated dialogues, turn-taking, number of characters, word used, and by analyzing text, illustration and pictureswhich coin with gender representative available in textbooksinvolving gender visibility (male or female) and gender stereotype. Accordingly, this paper is aiming at presenting and elaborating on kinds of over-representation of female and male characters that might be occurred and its pedagogical impact after understanding the issue of gender in textbooks. Â Key words: Gender bias, stereotype, characters, textbooks